5x+3-2x=-2x+5x+3

Simple and best practice solution for 5x+3-2x=-2x+5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3-2x=-2x+5x+3 equation:


5x+3-2x=-2x+5x+3

We simplify the equation to the form, which is simple to understand
5x+3-2x=-2x+5x+3

We move all terms containing x to the left and all other terms to the right.
+5x-2x+2x-5x=+3-3

We simplify left and right side of the equation.
0x=0

0=0

This equation is an identity, so all real numbers are solutions.

See similar equations:

| U+4=-12 | | x*x+12x+27=0 | | Ax+2=5 | | 2(x-6)+8=3(x+1)-4 | | 6x+7(x+9)= | | -6v=-3(-15v-17) | | -3(9+11w)=-(12+18w) | | 3.54x+1=12.5216+x | | x^20-2x^10+1=0 | | x^30-2x^10+1=0 | | -2(-19+16)=3(16z+20)+18 | | X^30+x^10+1=0 | | 4d=12-6(-2d+10) | | 2x-3/4=0 | | 5(-7g+15)=-5-15g | | 15+19y+19=-19y-3(-15y+19) | | f(x)=2x-3/4=0 | | t^4-t^2-1=0 | | 5j=5(6j-10) | | 3(2)+y=12 | | 3x/5-6=9 | | 3(6)+y=12 | | x+11=2x-1 | | -7+6(-4q+19)=20-3-19q | | 3(4)+y=12 | | 8(x-4)+9-3(x+5)+38=0 | | 29x+5=30x+1 | | 8x-7+3-x=14-4x | | 99=-3x | | 8.3u+19.72-18.2u=-19.88-14.4u | | x*x+x-42=0 | | 8x-7+3-x=14+4x |

Equations solver categories